Mg-doped hydroxyapatite nanoplates for biomedical applications: A surfactant assisted microwave synthesis and spectroscopic investigations - Mishra V.K.; Bhattacharjee B.N.; Parkash O.; Kumar D.; Rai S.B. (My University, 2025)
Nanoplates of Mg doped hydroxyapatite (Mg-HAp) were derived successfully and rapidly via microwave irradiation technique. Hydroxyapatite (HAp) is the hard tissues and main inorganic component in mammals. Different nanostructures of HAp exist in different parts of human bone but nanorods are very common due to its intrinsic nature to grow in rode-like structure under physiological as well as under applied ambient conditions in laboratory. On the addition of Mg at very low level (0.06 mol%) in pure HAp results the formation of 2-D plate-like nanostructures rather than rod-like which is the matter of interest. In this attempt our efforts have been focused on the study of effect of Mg incorporation on structural and spectroscopic properties of HAp prepared via microwave irradiation technique. This technique is preferred due to several advantages viz. very fast as well as homogeneous heating, time/energy saving and eco-friendliness. The calcium nitrate tetrahydrate (Ca(NO3) 2̇4H2O)) as a source of calcium, magnesium nitrate hexahydrate (Mg(NO3)2̇6H2O) as a source of magnesium, disodium hydrogen phosphate dihydrate (NaH2PO 4̇2H2O) as a source of phosphorous and sodium ethylene diamine tetra acetate (NaEDTA) as a surfactant were used as starting reagents. Sodium hydroxide (NaOH) pellets were employed to adjust the pH value of final solution. The solution of fixed pH value was kept into the microwave oven generating waves of frequency 2.45 GHz (water absorption frequency) and power 750 W for 8 min. The precipitate thus obtained was washed, centrifuged and then dried at 100 °C for 2 h. Dried powder was then calcined at 700°C for 2 h. The bright white powder thus obtained was characterized structurally using X-ray diffraction and SEM techniques and spectroscopically by FT-IR and Raman techniques. Structural and spectroscopic analysis revealed the formation of Mg doped HAp [Mg-HAp: (Ca4.94Mg0.06) (PO4) 3OH], nanoplates having average crystallite size of 26 nm as estimated by Scherrer's formula. © 2014 Elsevier B.V. All rights reserved.